Participation frameworks and gender in the narrative conversations of gypsy children - Poveda, David; Martín, Beatriz (Sociolinguistic Studies, 2003)
This paper presents an analysis of conversations around narratives of personal experience between a mixed-sex group of Gypsy children and non-Gypsy teachers and researchers. Data was obtained in two institutional contexts, a classroom in a public school and a class in a summer-school program, through semi structured interviews and conversations. Our analysis uses tools derived from conversation analysis and the ethnography of communication and examines two aspects of conversational organization. On the one hand, turn distribution according to the gender of participants and, on the other hand, the distribution of conversational roles in co-narrative episodes. In general terms, our findings show that girls play a much more active role in these conversations than boys. These results are discussed in the light of the institutional context in which they are produced and in relation to cultural patterns of the Gypsy community regarding men and women’s orientation towards work.